PEMANFAATAN APLIKASI TIKTOK SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR PUISI SISWA KELAS VIII SMP N 257 JAKARTA - puryanti, puryanti; Wulandari, Yosi; Sudibyo, Sarno R. (Ruang Kata, 2022)
Poetry learning in class VIII.9 SMPN 257 is less attractive, as a result, the learning objectives are not achieved and the results are less than optimal. Therefore, it is necessary to give efforts to increase student learning motivation through the use of technology, one of which is the Tiktok application. The purpose of this research is to increase students' motivation to learn poetry with the TikTok application. Classroom Action Research Methods or Classroom Action Research. This research involves collaborators or partners. This classroom action research was conducted at SMPN 257 Jakarta class VIII.9 starting from October 21, 2021 to Friday, November 5, 2021 or the odd semester of the 2021/2022 Academic Year. The research was carried out by distributing questionnaires and observations. The results of this class action research can be stated that there is a significant increase in 15 samples distributed to class VIII children. In the first cycle obtained 74% while in the second cycle obtained 82%. Further research is needed on the use of the TikTok application as another learning medium. Keywords: Enhancement, motivation, poetry learning, TikTok app